ISOLASI DAN KARAKTERISASI BAKTERI PROBIOTIK PADA SALURAN PENCERNAAN IKAN LAIS (Kryptopterus spp.) - Mustaqim '; Rodesia M Roza; Bernadeta Leni F (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Riau is one of provinces that has high diversity of lais fish. Lais fish is one of income sources for Riau community. Probiotics are "good" bacteria that are uninteutionally consumed alive until they reach an intestinal tract. Probiotics can also produce bacteriocins that have been known usefull against pathogens that are specific to some pathogen strains. The aims of this study were to isolate and characterize the probiotic bacteria found in the digestive tract of lais fish (Kryptopterus spp.). This study was conducted from November 2013 to January 2014 at the Microbiology Laboratory, Biology Departement University of Riau, Pekanbaru. The results of this study obtained 16 isolates of probiotic bacteria with all of the isolates belong to gram-positive bacteria with rod and circular shape. All of the isolates were non-motile, negative catalase, positive oksidase, the metil red test showed negative and positive result and the fisiological test showed that all of isolates were able to grow at the temperature of 25-37oC. All of the characterized isolates were grouped into Lactobacillus genus.